Can difficulties in laparoscopic cholecystectomy be anticipated preoperatively: evaluation of a scoring system - ., Sachin; Masanashetty, Srinivas N.; S., Sindhu; M., Devaprashanth (International Surgery Journal, 2020)
Background: Laparoscopic cholecystectomy is often associated with intra operative difficulties leading to increased intra and post-operative morbidity. Accurate prediction of a difficult laparoscopic cholecystectomy can reduce the complication rate, rate of conversion and overall medical cost. This study was an attempt to validate a scoring system developed to predict difficult laparoscopic cholecystectomy. Methods: 100 patients undergoing laparoscopic cholecystectomy were included. Details such as age, sex, BMI, previous surgical history, history of hospitalisation for biliary disease, sonographical wall thickness, pericholecystic collection and presence of impacted stone were noted. With these, pre-operative score was calculated using the scoring system. Intra operative details and complications were noted and were classified as easy, difficult and very difficult. Student t test and chi square test was used to test the difference of significance (p<0.05). Results: Male sex, higher BMI, a history of previous surgery, a history of prior hospitalisation for biliary disease, a palpable gall bladder, a thickened gall bladder wall, impacted stone and pericholecystic collection all had a statistically significant accurate prediction of the difficulty in laparoscopic cholecystectomy. The mean duration of surgery was 62.7±33.15 minutes. The scoring system developed by Randhawa et al predicted difficult laparoscopic cholecystectomy with a sensitivity of 77.8%, specificity of 78.1%, positive predictive value of 66.7% and a negative predictive value of 86.2%. Conclusions: The proposed scoring system predicted difficult laparoscopic cholecystectomy with a sensitivity of 77.8%, specificity of 78.1%, positive predictive value of 66.7% and a negative predictive value of 86.2%.